Economic Implications of Beneficiaries of the Pre-Employment Card Program in Lampung Province - Robby Kurniawan, Muhammad; Budiarty DA, Ida; Ciptawaty, Ukhti (Lafadz Jaya Publisher, 2024)
The pre-employment card program is a policy designed by the government to expand employment opportunities, increase competency and competitiveness for the workforce. This research aims to analyze the implications of the pre-employment card program on the economic conditions of beneficiaries of the pre-employment card program in Lampung Province from 2020-2022. The analytical method used in this research is the qualitative descriptive analysis method. The type of data used in this research is primary data obtained directly from beneficiaries of the pre-employment card program in Lampung Province. The research results show that the pre-employment card program has implications for the economy of the beneficiaries of the pre-employment card program in Lampung Province, especially in increasing income, cost efficiency in seeking training, increasing purchasing power, business capital and also financial inclusion for pre-employment card beneficiaries in Lampung Province.